Portraying Indonesian English language teachers’ readiness for teaching online classes - Tutyandari, Caecilia; Purnamaningwulan, Rina Astuti (Englisia Journal, 2023)
Amidst the proliferation of the COVID-19 virus in Indonesia, educators, students, and educational institutions are still adapting to the implementation of online instructional methods. This investigation delves into the preparedness of English as a Foreign Language (EFL) teachers in conducting online classes, as well as the obstacles they encounter while doing so. The purpose of this study is to serve as a foundation for schools to develop effective strategies for administering online classes, and to equip teachers with the necessary skills to facilitate learning in the online realm. This current research employed a mixed-method design in order to gather the essential information required to address the research questions at hand. The data was collected through the utilization of an online Likert-scale questionnaire and focus group interviews. The questionnaire was utilized to evaluate teachers' preparedness across three dimensions: Technological Pedagogical Content Knowledge (TPACK), teachers' presence, and institutional support. A total of 336 EFL teachers from various high schools in Indonesia voluntarily participated in the survey, while nine participants took part in the focus group interviews. The findings of this investigation indicate that, on average, EFL teachers possess a moderate to high level of perceived preparedness across the three aforementioned dimensions. This suggests that the majority of teachers are adequately equipped to engage in distance learning. However, the present findings also shed light on the concerns expressed by teachers during the online teaching and learning process. These challenges encompass the proficiency of teachers in utilizing TPACK, the workload imposed on teachers, the psychological well-being of students, and the support provided by educational institutions. Furthermore, this exploration provides a concise overview of the intricate nature of teachers' preparedness.